The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ab.21675
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aggression in adolescence: The interrelation between (a lack of) empathy and social goals

Abstract: In an attempt to explain the inconsistent findings and overall weak relation between empathy and aggression, we focused on the role of emotional empathy (emotions of concern, compassion or sympathy toward a (potential) victim), agentic goals (the desire to be dominant during social interaction with peers) and their interplay (mediation or moderation) in the prediction of proactive aggression (learned instrumental behavior) in adolescence. Data were collected from 550 young Dutch adolescents, who filled out mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
(89 reference statements)
1
22
0
Order By: Relevance
“…The differences in scores by sex in the different types of aggression were only significant in Overt proactive aggression and Relational proactive aggression, where boys scored higher than girls in both. These results are in agreement with those found by Rieffe et al [17] where boys had high percentages in both proactive and reactive aggression, but not with Van Hazebroek et al [18] who found that it was reactive aggression where boys predominated, and no sex differences were found in proactive aggression. The results for the characterization of victim and aggressor, according to each of the aggression scales, showed that the group of aggressors had significantly higher means on all the scales than the nonaggressors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The differences in scores by sex in the different types of aggression were only significant in Overt proactive aggression and Relational proactive aggression, where boys scored higher than girls in both. These results are in agreement with those found by Rieffe et al [17] where boys had high percentages in both proactive and reactive aggression, but not with Van Hazebroek et al [18] who found that it was reactive aggression where boys predominated, and no sex differences were found in proactive aggression. The results for the characterization of victim and aggressor, according to each of the aggression scales, showed that the group of aggressors had significantly higher means on all the scales than the nonaggressors.…”
Section: Discussionsupporting
confidence: 92%
“…There are also gender differences in the different types of aggression [15], where boys have higher percentages of reactive and proactive aggression than girls [16,17]. However, van Hazebroek, Olthof, and Goossens [18] found higher levels of reactive aggression in the group of boys than the group of girls, and no gender differences was found in proactive aggression.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting final sample consisted of 549 adolescents (49.4% boys; M age = 12.5 years, SD = 0.6 years). This sample was previously included in a study about the interrelations between empathy and social goals in explaining adolescents’ aggressive behavior (van Hazebroek, Olthof, & Goossens, ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have analysed the relationships between the levels of empathy and the development of violent, aggressive and victimisation behaviours in different populations, showing that lower levels of empathy increase the development of manifest and relational aggressiveness, while high levels of empathy decrease the emergence of violent behaviours, due to the fact that when the individual is able to identify other people’s feelings, he or she avoids causing any harm [26,27]. Regarding the association between self-concept and empathy, a positive relationship between both psychological factors has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%